Analysis of a Free Piston Linear Generation System - Mat Daud, Ahmad Taqiyuddin (2018)
Incomplete combustion has been discussed as the major thing that contributes to emission’s problem. Researcher and engineers have developed many solutions to minimize the problem and one of the alternative is, using free piston linear generator (FPLG). Although many of them still opt to improve the current conventional engine, FPLG has been justified to be more advance in terms of technology and power efficiency. Besides FPLG is suitable to be run by any types of fuel which makes it more flexible in terms of preparing for the situation where depleting of fossil fuels is getting more serious. But in this moment, FPLG is still not commercialized yet and this project’s report will try to cover starting process and stability of the engine during running testing.